A Survey of Privacy Solutions using Blockchain for Recommender Systems: Current Status, Classification and Open Issues. (31st May 2021) - Abduljabbar, Tamara Abdulmunim; Tao, Xiaohui; Zhang, Ji; Zhou, Xujuan; Li, Lin; Cai, Yi
Abstract: Due to the rapid growth of Internet, E-commerce and Internet of Things, people use Web based services for most of their needs including buying items, reading books, watching online shows etc. Several companies are using recommender systems to influence people's choices based on their likings, behaviours etc. Hence, people fear that their privacy is violated. Also, some of the online applications are not safe and secure. One way to overcome the privacy related issues is using secured solutions such as incorporating blockchain technologies for privacy-based applications. The decentralized nature of blockchain technologies have resolved several security, and authentication problems of Internet of Things systems. In this paper, we conduct a comprehensive survey on the privacy solutions for recommender systems emphasising current status, classification and open issues. We also discuss blockchain technology, including its structure as well as applications of blockchain technology for privacy solutions of recommender systems. Furthermore, we discuss the limitations and delve into future trends that blockchain technology can be adapted for privacy-base applications in the years to come.